Sub-Saharan Political Cultures of Deceit in Language, Literature, and the Media, Volume II
XXIII, 428 p. 4 illus., 2 illus. in color.
Keywords: This two-volume set charts a cross-disciplinary discursive terrain that proffers rich insights about deceit in contemporary postcolonial Sub-Saharan African politics. In an attempt to produce a nuanced and multifaceted academic dialoguing platform, the two volumes have a particular focus on the aspects of treachery, fear of difference (oppositional politics), and discourses/semiotics of mis/self-representation. The major aim of the proposed volumes is to contribute toward the often problematized conversations about the unfolding (post)colonial Sub-Saharan world which is topical in decolonial and Pan-African studies. The volumes seek to place political thinking and postcolonial political systems under the scholarly gaze with the view to highlight and enhance the participation of African cross-disciplinary scholarship in the postcolonial political processes of the continent. Most significantly, it is through such probing of the limitations of our own disciplinary perspectives which can help us appreciate the complexity of the postcolonial Sub-Saharan African politics. The first volume uses Zimbabwe as a case study, while the second volume examines postcolonial politics in Sub-Saharan Africa more broadly. The first volume uses Zimbabwe as a case study, while the second volume examines postcolonial politics in Sub-Saharan Africa more broadly. The first volume uses Zimbabwe as a case study, while the second volume examines postcolonial politics in Sub-Saharan Africa more broadly. Esther Mavengano is Lecturer in English and Media Studies, Great Zimbabwe University, Zimbabwe. She is a Research Fellow at the Research Institute for Theology, and Religion, College of Human Sciences, UNISA, South Africa and a von Humboldt Postdoctoral Fellow in the Department of English, Institute of English and American Studies, Faculty of Linguistics, Literature and Cultural Studies, Technology University Dresden, Germany. Isaac Mhute is Associate Professor of Language, Literature and Culture Studies, Midlands State University, Zimbabwe.